Urban heat island analysis on land use planning in greater Kuala Lumpur through remote sensing applications - Nordin, Atikah; Hj. Mohd. Noor, Norzailawati; Ibrahim, Illyani (2016)
The process of urban growth gives impacts to the form and structure of an urbanised area and the temperature is increasing due to continuous human activities and development within the area. This paper attempts to study an integrated approach of using remote sensing and GIS techniques in determining the Urban Heat Island (UHI) for Bukit Bintang Kuala Lumpur by analysing the formation and intensity of Land Surface Temperature (LST) and Normalized Difference Vegetation Index (NDVI). The analysis of LST and NDVI are used to determine the relationship between the surface temperature, green spaces and land use developments towards UHI phenomenon with extracting the Landsat TM5. The result shows that Landsat TM5 could provide an accurate map and give detailed descriptions on the LST and NDVI across the study area. Spatial distributions of surface temperature demonstrated that there is a positive and close relationship between the heat islands and urban growth, whereas the LST and NDVI have an indirect relationship with a correlation coefficient of -0.083562. This indicates that the impact of green land on UHI is negative, which suggests that the green land can weaken the UHI effect. However, there is a positive correlation of 0.08386 between LST and Land Use which means that the built-up land can strengthen the UHI effect in the Bukit Bintang study area. The temperature at the centre of urbanization of Bukit Bintang Walk is in the range of 32°C until 34ºC, where the famous crossing is located. The results achieved on the correlation among LST, NDVI and Land Use can be used by governments, agencies, planners to know which operation should be used for various process such as urban growth monitoring.